Reliability engineering : Theory and practice - Birolini, Alessandro (Springer Berlin Heidelberg, 2014)
This book shows how to build in, evaluate, and demonstrate reliability and availability of components, equipment, systems. It presents the state-of-theart of reliability engineering, both in theory and practice, and is based on the author's more than 30 years experience in this field, half in industry and half as Professor of Reliability Engineering at the ETH, Zurich. The structure of the book allows rapid access to practical results. This final edition extend and replace all previous editions. New are, in particular, a strategy to mitigate incomplete coverage, a comprehensive introduction to human reliability with design guidelines and new models, and a refinement of reliability allocation, design guidelines for maintainability, and concepts related to regenerative stochastic processes. The set of problems for homework has been extended. Methods & tools are given in a way that they can be tailored to cover different reliability requirement levels and be used for safety analysis. Because of the Appendices A6 - A8, the book is also self contained from a mathematical point of view, and can be used as a text book or as a desktop reference, with a large number of tables (60), figures (190), and examples (210 of which 70 as problems for homework) to support the practical aspects.